2015
DOI: 10.1021/acs.jpcc.5b03211
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complex Porosity of Transition Aluminas by 129Xe NMR Spectroscopy

Abstract: Crystalline mesoporous γ-, δ-, and θ-alumina samples with complex porosity and various surface areas (70 to 330 m 2 /g) were characterized by 129 Xe NMR spectroscopy and nitrogen adsorption. Experimental conditions have been optimized to measure 129 Xe NMR chemical shifts independent of the nature of the surface and solely dependent on the pore size. Xenon adsorption constants have been determined from xenon adsorption isotherms and from the fit of the chemical shift versus volume to surface ratio (V/S) curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…129 Xe NMR was initially applied to crystalline microporous oxides such as zeolites and clathrates [51,52]. Later, its application range was extended to amorphous mesoporous materials such as silica [53,54], alumina [55] and carbonaceous materials [56]. It has been demonstrated that the introduction of a liquid or solid medium into a mesoporous material slows down the inter-pore exchange of xenon, 5 which facilitates the determination of pore size distribution [ 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…129 Xe NMR was initially applied to crystalline microporous oxides such as zeolites and clathrates [51,52]. Later, its application range was extended to amorphous mesoporous materials such as silica [53,54], alumina [55] and carbonaceous materials [56]. It has been demonstrated that the introduction of a liquid or solid medium into a mesoporous material slows down the inter-pore exchange of xenon, 5 which facilitates the determination of pore size distribution [ 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…129 Xe NMR spectroscopy has successfully been applied to investigate natural samples such as soil [62], clays and pillared clays [63], coals [56] and stones [64], and it is has also been exploited to determine the lattice boron content [65]. The experimentally determined correlations between the chemical shift and pore size [50,51,54,55,61]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we explored the complex porosity of transition aluminas with 129 Xe NMR [139]. In these aluminas the porosity is generated by the aggregation of non-porous crystalline platelets (about 2-20 nm in size).…”
Section: Porosity Measurement Of Alumina Catalystsmentioning
confidence: 99%
“…[35][36][37] Recently, we established a new correlation adapted to transition aluminas. 17 When the exchange of xenon atoms between different types of environments is not too fast (exchange rate smaller than the frequency difference between the NMR signals characteristic of each environment), the spectra show as many signals as there are types of environments. 38 As shown above, it is the case of Al_224_b alumina which presents a bimodal porosity.…”
Section: Exchange Of Xenon Between Different Porosities or Between Pomentioning
confidence: 99%
“…Very recently, a correlation between the 129 Xe chemical shift and the pore size was established for alumina supports. 17 There are several reviews on the applications of xenon NMR to microporous materials. [18][19][20] In contrast to the most common techniques such as smallangle X-ray or neutron scattering, and gas adsorption, 2D exchange spectroscopy (EXSY) 129 Xe NMR can provide direct information on how pores are connected and, therefore, a better understanding of the pore structure, the uniformity of the adsorption sites and the pore connectivity between different adsorption regions.…”
Section: Introductionmentioning
confidence: 99%